Pendampingan Program Peningkatan Pemahaman Gaya Belajar dan Gaya Berfikir pada Guru TK Dharma Wanita Legokulon Kasreman Ngawi - Arih Merdekasari; Ruliana Khasanah (Jurnal Abdikarya Pembangunan, 2023)
Abstract: Teachers have an important role in the learning process. The teacher's understanding of learning styles and thinking will make the learning process better. Teachers will find it easier to create a balanced teaching style by paying attention to the learning styles of all students. Teachers can provide material according to students' learning styles so they can optimize their learning outcomes. This service uses a Participated Action Research approach. Mapping the problem begins with conducting interviews with the principal of Dharma Wanita Kindergarten Legokulon Kasreman Ngawi. The formulation of the action is carried out by taking into account input from the school principal and teachers. Action activities include, preparation of material learning styles and thinking styles, preparation of learning styles and thinking styles questionnaires, filling out of learning styles and thinking styles questionnaires. Delivery of the results of learning style difficulties and discussions for better teacher understanding. the result is that the teacher knows his learning style and thinking style. The learning style that appears the most is auditory and the thinking style that appears is abstract random. Follow-up discussions on balancing teacher learning styles which have implications for teacher teaching styles. Keywords: Child, Learning style, Teacher, Thinking Style Abstract: Guru memiliki peranan penting dalam proses pembelajaran. Pemahaman guru terhadap gaya belajar dan berfikirnya akan membuat proses pembelajaran menjadi lebih baik. Guru akan lebih mudah membuat gaya mengajar yang seimbang dengan memperhatikan gaya belajar seluruh siswanya. Guru dapat memberikan materi sesuai denga gaya belajar siswa sehingga dapat mengoptimalkan hasil belajarnya.. Pengabdian ini mengunakan pendekatan Participated Action Research. Pemetaan masalah dimulai dengan melakukan wawancara pada kepala sekolah TK Dharma Wanita Legokulon Kasreman Ngawi. Perumusan aksi dilaksanakan dengan mempertimbangkan masukan dari kepala sekolah dan guru. Kegiatan aksi meliputi , penyusunan materi gaya belajar dan berfikir, penyusunan kuesioner gaya belajar dan gaya berfikir, pengisian kuesioner gaya belajar dan gaya berfikir . Penyampaian hasil pemetaan gaya belajar dan diskusi untuk pemahaman guru yang lebih baik. Hasilnya guru mengetahui gaya belajar dan gaya berfikir yang dimilikinya. Gaya belajar yang paling banyak muncul adalahauditorial dan gaya berfikir yang muncul adalah acak abstrak Tindak lanjutnya melakukan diskusi terhadap penyeimbangan gaya belajar guru yang berimplikasi pada gaya mengajar guru. Keywords: Anak, gaya Belajar, Gaya berfikir, Guru